Skin aging from the medical point of view, literature review in the aspect of tissue stimulants - Branewska, Justyna; Imioło, Jan; Ostrowska, Barbara; Matysek, Mikołaj; Olszanicka, Anna; Maciąg, Anna; Niemiec, Rafał; Hop, Izabela; Kołodziejczyk, Kacper; Galas, Adam (Journal of Education, Health and Sport, 2023)
Introduction and purpose of the work. Aesthetic medicine currently has many methods to keep our skin in the best possible condition, and one of these methods is the use of tissue stimulators. The purpose of the following paper is to analyze, present and apply tissue stimulators in anti-aging prevention. Review methods. The paper is based on a review of literature about tissue stimulators, aesthetic medicine and anti-aging therapy. Most of the publications used were from Pubmed and Google Scholar electronic databases. State of the art description. Aesthetic medicine is a department that over the past few years has been closely associated with the slowing down of skin aging processes. In humans, over the years, proliferative processes slow down, the rate of collagen and elastin degradation increases, and the intercellular matrix is reduced. Substances known as tissue stimulators used in anti-aging therapies mean that the above processes can be delayed. Conclusion. The expectations of patients visiting aesthetic medicine clinics regarding activities that improve their appearance are increasing. They are unable to accept their own aesthetic defects, which is why they often strive for unnatural effects. Tissue simulator treatments can be a valuable way for patients to maintain healthy and rejuvenated skin.